2009
DOI: 10.1371/journal.pone.0005780
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Associated Plasminogen Binding of Cryptococcus neoformans Promotes Extracellular Matrix Invasion

Abstract: BackgroundThe fungal pathogen Cryptococcus neoformans is a leading cause of illness and death in persons with predisposing factors, including: malignancies, solid organ transplants, and corticosteroid use. C. neoformans is ubiquitous in the environment and enters into the lungs via inhalation, where it can disseminate through the bloodstream and penetrate the central nervous system (CNS), resulting in a difficult to treat and often-fatal infection of the brain, called meningoencephalitis. Plasminogen is a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 86 publications
4
94
0
Order By: Relevance
“…Previous work has shown that enolase binds to hPlg through lysine residues (33,47). We thus examined if binding of rPbEno was lysine dependent by using competitive antagonism with the lysine analog ε-ACA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has shown that enolase binds to hPlg through lysine residues (33,47). We thus examined if binding of rPbEno was lysine dependent by using competitive antagonism with the lysine analog ε-ACA.…”
Section: Resultsmentioning
confidence: 99%
“…After adherence, the next step must be to overcome the barriers imposed by epithelial tissues and ECM. The proteolytic activity achieved by subversion of host proteases by pathogens, such as plasmin, has been shown to be important during the process of many types of infections (47,51).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the PLG/PLA binding has been described to facilitate the keratinocyte invasion by Streptococcus pyogenes (32). Furthermore, it has been reported that the fungal pathogen Cryptococcus neoformans coated with PLG promotes extracellular matrix (ECM) invasion (33). Surprisingly, the cellular transmigration efficiency of leptospires treated only with PLG and lacking uPA was higher than that in the untreated control.…”
Section: Discussionmentioning
confidence: 99%